Collected tales, poems, and other writings of Edgar Allan Poe - Poe, Edgar Allan (Bloomsbury Academic, 2023)
This collection brings together more than fifty of Edgar Allan Poe's most important stories, poems, and critical writings, which established him as one of the most distinctive voices in American Literature, in a single accessible volume.Alongside annotated texts of each work, it also includes a complete Reader's Guide to Poe's work to help readers explore the contexts, style, and reception of his writing from his own time to today. An essential resource for students and teachers of Poe, this book includes stories such as 'The Fall of the House of Usher', 'The Tell-Tale Heart', and 'The Purloined Letter' as well as his Gothic narrative poem 'The Raven' and some of his most significant critical writings.